EFEKTIVITAS E-MODUL INTERAKTIF BERBASIS PEMBELAJARAN PROJECT DITINJAU DARI KEMAMPUAN LITERASI MATEMATIS DAN KEPERCAYAAN DIRI MAHASISWA - Susanto, Edi; Susanta, Agus (Universitas Muhammadiyah Ponorogo, 2022)
The implementation of distance learning at every level of education, significantly higher education, has various obstacles. One of them was the lack of teaching materials that can support students to learn both guided and independent. Learning resources that were commonly used did not interactively support learning. This study aimed to determine the effectiveness of interactive e-modules based on project-based learning in mathematical literacy skills and student confidence in number theory courses. The type of research used was quasi-experimental with a quantitative approach. The research subjects were students of the 2021 mathematics education study program, which consisted of two classes with 32 experimental classes and 36 control classes. Technique sample used a census where each class was selected and determined treatment. Data collection techniques were used tests with literacy ability test instruments and self-confidence questionnaires. Data analysis with descriptive analysis and hypothesis testing using MANOVA and the effectiveness of learning with interactive e-modules were analyzed using a one-sample t-test.The results showed that the application of project-based learning-based interactive e-modules was effective in students' literacy skills, with a t-count result of 6.949 and a significance level of 0.000. The use of e-modules is more effective than the control class, with an average literacy ability of 81.25 in the experimental class and 62.91 for the control class. I am judging from the adequate self-confidence with a high category and the results of t count of 4.179 significant at 0.05 alpha. The results of the Manova analysis show that the application of interactive e-modules is more effective in terms of literacy skills and student self-confidence, with a significant Hotelling's trace of 0.000